2019
DOI: 10.3389/fpls.2019.00184
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of a Camelina sativa Spring Panel

Abstract: There is a need to explore renewable alternatives (e.g., biofuels) that can produce energy sources to help reduce the reliance on fossil oils. In addition, the consumption of fossil oils adversely affects the environment and human health via the generation of waste water, greenhouse gases, and waste solids. Camelina sativa , originated from southeastern Europe and southwestern Asia, is being re-embraced as an industrial oilseed crop due to its high seed oil content (36–47%) and high unsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
119
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(144 citation statements)
references
References 51 publications
21
119
2
2
Order By: Relevance
“…The transition SNPs were more frequent than transversion SNPs, indicating that transition mutations are more tolerable to natural selection (27). A similar result was also found in other species such as Camelina sativa (28), Camellia sinensis (29), Hevea brasiliensis (30) and Brassica napus (31,32), that may be due to synonymous mutations in protein-coding regions (33). We also calculated PIC and expected heterozygosity (He) for each marker.…”
Section: Discussionsupporting
confidence: 61%
“…The transition SNPs were more frequent than transversion SNPs, indicating that transition mutations are more tolerable to natural selection (27). A similar result was also found in other species such as Camelina sativa (28), Camellia sinensis (29), Hevea brasiliensis (30) and Brassica napus (31,32), that may be due to synonymous mutations in protein-coding regions (33). We also calculated PIC and expected heterozygosity (He) for each marker.…”
Section: Discussionsupporting
confidence: 61%
“…Polymorphism information content ( ) indicates measures of genetic diversity (Botstein et al 1980;Niu et al 2019). values for this study ranges from 0.142 to 0.375 (with an average of 0.18), in congruence with the maximum value of 0.375 for biallelic loci (Nei 1987;Botstein et al 1980;Luo et al 2019 'from the identified genetic groups reflects the rate at which variation is lost and may predict the ability to respond to future changes/breeding strategy and significance of conservation approach to genetic diversity and adaptive variation in cassava breeding in Brazil. The estimate of H gives a better understanding of the present and future importance of genetic drift of cassava populations and useful information of germplasm management in Brazil.…”
Section: Genetic Diversity Estimationsupporting
confidence: 84%
“…While genetic diversity and population structure have been evaluated in related crop species including rapeseed and camelina [18,19], few evaluations of natural pennycress germplasm have been completed. Forty-one pennycress accessions were evaluated for variation in seed size and fatty acid profile, but no genetic analysis was completed [20].…”
Section: Introductionmentioning
confidence: 99%